Peran Manajerial Kepala Sekolah Dalam Mengembangkan Kegiatan Ekstrakurikuler Di Sekolah (Studi Kasus MTs Keppe Kecamatan Larompong): (The Managerial Role of the Principal in Developing Extracurricular Activities in Schools (Case Study of MTs Keppe, Larompong District) - Tahrim, Tasdin (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2020)
Extracurricular activities are non-academic activities that support academic activities. Extracurricular activities are very important in growing and developing students' skills, both in their personal activities and community issues so that students are ready to face the world of work and their future. But in practice, extracurricular activities sometimes do not get a balanced portion compared to academic activities. This needs to be the concern of the Principal as the full control and manager in all program activities in the school. The study was conducted at MTs Keppe Larompong Subdistrict to find out how the managerial role of the Principal in developing extracurricular activities in schools and the obstacles encountered. Through the method of field research (Field Research) obtained the results that the Principal of MTs Keppe Larompong District has carried out its managerial role well. This is proven that currently there have been carried out six types of extracurricular activities namely Scouting, PMR, SSB Si Jagoraga, Drum Band, SPM and Arts and Culture. In addition, the fulfillment of facilities and infrastructure for extracurricular activities has been carried out by the school principal. The Principal also plays an active role in monitoring activities ranging from the appointment of the Teacher Guidance for each activity, conducting supervision, opening up the domain of coordination to the activity development innovation program. The obstacles faced by the Principal of MTs Keppe, Larompong Subdistrict are the lack of activity funds and the lack of competent human resources as co-teachers of extracurricular activities. Abstrak. Kegiatan ekstrakurikuler merupakan kegiatan non-akademik yang mendukung kegiatan akademik. Kegiatan ekstrakurikuler sangat penting dalam menumbuhkan dan mengembangkan keterampilan (skill) siswa, baik itu dalam kegiatan pribadinya maupun soisal masyarakat agar siswa siap menghadapi dunia kerja dan masa depannya. Namun pada praktiknya, kegiatan ekstrakurikuler kadang kala tidak mendapat porsi seimbang disbanding kegiatan akademik. Hal ini perlu menjadi perhatian Kepala Sekolah sebagai pemegang kendali penuh dan manajer dalam semua program kegiatan di sekolah. Penelitian dilakukan di MTs Keppe Kecamatan Larompong untuk mengetahui bagaimana peran manajerial Kepala Sekolah dalam mengembangkan kegiatan ekstrakurikuler di sekolah dan kendala yang dihadapi. Melalui metode penelitian lapangan (Field Research) diperoleh hasil bahwa Kepala Sekolah MTs Keppe Kecamatan Larompong telah menjalankan peran manajerialnya dengan baik. Hal ini dibuktikan bahwa saat ini telah dilaksanakan enam jenis kegiatan ekstrakurikuler yaitu Pramuka, PMR, SSB Si Jagoraga, Drum Band, SPM serta Seni dan Budaya. Selain itu, pemenuhan sarana dan prasarana kegiatan ekstrakurikuler telah dilakukan oleh Kepala Sekolah. Kepala Sekolah juga berperan aktif dalam memonitoring kegiatan mulai dari penunjukkan guru Pembina masing-masing kegiatan, melakukan pengawasan, membuka ranah koordinasi hingga program inovasi pengembangan kegiatan. Adapun faktor kendala yang dihadapi yang dihadapi oleh Kepala Sekolah MTs Keppe Kecamatan Larompong yaitu minimnya dana kegiatan dan kurangnya sumber daya manusia yang kompeten sebagai guru pendamping kegiatan ekstrakurikuler.